2021
DOI: 10.3390/ijms221910775
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Pd2Spm (Spermine) Complex on the Metabolism of Triple-Negative Breast Cancer Tumors of a Xenograft Mouse Model

Abstract: The interest in palladium(II) compounds as potential new anticancer drugs has increased in recent years, due to their high toxicity and acquired resistance to platinum(II)-derived agents, namely cisplatin. In fact, palladium complexes with biogenic polyamines (e.g., spermine, Pd2Spm) have been known to display favorable antineoplastic properties against distinct human breast cancer cell lines. This study describes the in vivo response of triple-negative breast cancer (TNBC) tumors to the Pd2Spm complex or to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…As previously reported, the initial rate of formazan formation may serve as an indicator of complex I activity and the pyruvate transport rate [37], indicating a disruption of mitochondrial functional activity, conditioning cell metabolism and, therefore, cell viability. Previous metabolomic studies of osteosarcoma in mice in the presence of Pd 2 Spm have highlighted its impact on osteoblastic amino acid metabolism [38], as well as numerous changes in specific amino acids, nucleotides and derivatives; membrane precursors (choline and phosphoethanolamine); dimethylamine; fumarate and guanidine acetate [23]. These data prompt the need for similar metabolomic studies in order to clarify the impact of the currently investigated Pd 3 Spd 2 on TNBC, which may help to understand why different palladium-based chelates (namely, dinuclear with Spm and trinuclear with Spd) exhibit comparable antineoplastic activities towards TNBC, as reported in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported, the initial rate of formazan formation may serve as an indicator of complex I activity and the pyruvate transport rate [37], indicating a disruption of mitochondrial functional activity, conditioning cell metabolism and, therefore, cell viability. Previous metabolomic studies of osteosarcoma in mice in the presence of Pd 2 Spm have highlighted its impact on osteoblastic amino acid metabolism [38], as well as numerous changes in specific amino acids, nucleotides and derivatives; membrane precursors (choline and phosphoethanolamine); dimethylamine; fumarate and guanidine acetate [23]. These data prompt the need for similar metabolomic studies in order to clarify the impact of the currently investigated Pd 3 Spd 2 on TNBC, which may help to understand why different palladium-based chelates (namely, dinuclear with Spm and trinuclear with Spd) exhibit comparable antineoplastic activities towards TNBC, as reported in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, as for the analogous polynuclear Pt(II) chelates, these agents, containing more than one metal center, can bind to the DNA's helix at more than one site and through long-range interstrand adducts, which prompts more severe and unrepairable damage compared to conventional, mononuclear Pt(II) drugs. Additionally, the impact of Pd(II) compounds has been reported to also occur on other targets apart from DNA, such as proteins [21], oxidative species [22,23] or even intracellular water [24]. The therapeutic effectivity of these type of Pt(II) agents results, at least in part, from the formation of Pt-DNA adducts (through covalent binding to the bases), which induces DNA damage and triggers apoptosis [17].…”
Section: Introductionmentioning
confidence: 99%
“…Promising antiproliferative activities via apoptosis induction in preclinical BC cellular models, including cisplatin-resistant cells, have also emerged during the trialling of binuclear Pd(II) complexes, conceived using biogenic polyamines (e.g., spermine) and named Pd2Spm. In addition to showing additional antiangiogenic and antimetastatic activities in vivo, Pd2Spm derivatives seem to share profitable pharmacokinetic and toxicological profiles; thus, additional investigations towards prospective clinical applications are warranted [ 203 , 204 ]. These findings still confirm attractive bioactivities for many Pd(II) derivatives working against BC tumour models, including TNBC phenotypes [ 191 ].…”
Section: Palladiummentioning
confidence: 99%
“…Metabolomics has been extensively highlighted as a valuable tool towards the understanding of the interplay between drugs and cellular metabolism in breast cancer . Indeed, metabolomics of CDX mice with TNBC showed that, compared to cDDP, Pd 2 Spm induced (i) pronounced metabolic disturbances in tumor metabolism (energy, membrane, nucleotides, and one-carbon metabolisms), possibly reflecting a different mechanism of action of the Pd­(II) complex, and (ii) an enhanced neuroprotective response of brain, along with lower impact on liver. , Furthermore, Pd 2 Spm administration induced initial metabolic deviations in healthy BALB/c mice, which, however, returned to control levels faster (within 48 h) than with cDDP, namely, in kidney, liver, breast tissue and brain. , This corroborated other reports of lower in vivo toxicity of the Pd­(II) compound, compared to that of cDDP. , …”
Section: Introductionmentioning
confidence: 99%